Addition of spent coffee grounds to reduce cement usage and increase cement mortar strength - Yee, Jia Jun; Khong, Sheh Ching; Tee, Kong Fah; Jolius, Gimbun; Chin, Siew Choo (Emerald Publishing Limited, 2025)
This paper elucidates potential of spent coffee grounds (SCG) to reduce cement usage in a cement mortar mix by studying SCG as partial cement replacement in mortar production. Surface morphology and elemental composition of SCG were characterised using scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy and X-ray fluorescence analysis. With limited research on SCG incorporation in cementitious systems, this work evaluates setting time, fresh properties, and mechanical performance of SCG cement mortar at replacement levels ranging from 0% to 10%. Mortar specimens were water cured for periods between 7 and 90 days, after which compressive and flexural strengths were assessed. Optimisation results indicated that mortar containing 1.48% SCG, cured for 78 days, achieved highest compressive strength of 34.17 MPa. Thermogravimetric analysis revealed increased calcium carbonate formation in SCG-modified mortar, with no significant changes to other hydration products, despite reduced cement content. Durability testing demonstrated lower strength loss in SCG mortar compared with conventional mixes. These findings indicate SCG incorporation enhances both strength and durability, supporting its application as a sustainable construction material aligned with United Nations Sustainable Development Goals, specifically Goals 9 (Industry, Innovation and Infrastructure), 11 (Sustainable Cities and Communities), and 13 (Climate Action).